Ejercicio físico y obesidad (Original) (Revista científica Olimpia, 2022)
Throug hout the world, it has noted the need to counter act the wrong of the overweight. However, the current society do es not know the consequences that this occasion long-term, by removing you the importance that is deserved. Between the non-farmacological strategiesn more used for the control of the corporal weig thit finds the physical exercise. The type of investigation carried out was bibliographical, with the too much analysis of 100 scientific coming documents of grateful corresponding database stop the period 2010-2021 that it permitted identify information truth full, is necessary and fundamental fot the topic of the promotion of the physical activity foot de crease the overweight. For which the of the correct weight effectivelong-termloss depends of permanent changes in the quality of the diet, the intake of energy and theactivity.Thequestion i show tointegratetheneverdailyphysicalexercisebybeingimportantthe time thatitdedicatesyou, preferably a 30-minutes minimum.